Generation of test cases using UML models (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Software Testing plays an important role in Software development because it can minimize the development cost. UML is widely used in the software development, there consists of the designing and coding of the software. Designing phase is done with the help of the UML models, which consists of the sequence diagrams, activity diagrams, use case diagrams, state chart diagrams etc. After designing of the system, the next task is coding. Since the software development is time and human resource consuming, the reduction of consumption is done with the help of the code generation automatically. This work mainly focus on the UML sequence diagram and state chart diagram as the model. We Propose a Technique for Test Case Generation using UML Models. UML models give a lot of Â information that should not be ignored in testing. An innovative approach of generating test cases from the combination of UML design diagrams has been discussed in this paper. Present work used an approach where sequence diagram and state chart diagram has been used to generate test cases. The test cases thus generated are suitable for dynamic testing of system.